Toward evidence‐based severity assessment in rat models with repeated seizures: II. Chemical post–status epilepticus model. (31st August 2019) - Koska, Ines; van Dijk, Roelof Maarten; Seiffert, Isabel; Di Liberto, Valentina; Möller, Christina; Palme, Rupert; Hellweg, Rainer; Potschka, Heidrun
Abstract: Objective: Considering the complexity of neuronal circuits and their epilepsy‐associated alterations, epilepsy models cannot be completely replaced by in vitro experimental approaches. Decisions about ethical approval of in vivo studies require a thorough weighing of the animal's burden and the benefit regarding the expected gain in knowledge. Methods: Based on combined behavioral, biochemical, and physiological analyses, we assessed the impact on animal well‐being and condition in different phases of the pilocarpine post–status epilepticus (SE) model in rats. Results: As a consequence of SE, increased levels of impairment were evident in the early postinsult phase and late chronic phase, whereas only mild impairment was observed in the interim phase. Parameters that stood out as sensitive indicators of animal distress include burrowing, which proved to be affected throughout all experimental phases, saccharin preference, fecal corticosterone metabolites, heart rate, and heart rate variability. Significance: The cumulative burden with temporary but not long‐lasting phases of more pronounced impairment suggests a classification of severe as a basis for laboratory‐specific prospective and retrospective evaluation. Among the parameters analyzed, burrowing behavior and saccharin preference stand out as candidate parameters that seem to be well suited to obtain information about animal distress in epileptogenesis models.